Mosaic genome‐wide paternal uniparental disomy after discordant results from primary fetal samples and cultured cells. Issue 4 (4th January 2023) - Mastromoro, Gioia; Guadagnolo, Daniele; Marchionni, Enrica; Torres, Barbara; Goldoni, Marina; Onori, Annamaria; Bernardini, Laura; De Luca, Alessandro; Torrente, Isabella; Pizzuti, Antonio
Abstract: Mosaic genome‐wide paternal uniparental disomy (GWpUPD) is a rare condition in which two euploid cell lines coexist in the same individual, one with biparental content and one with genome‐wide paternal isodisomy. We report a complex prenatal diagnosis with discordant results from cultured and uncultured samples. A pregnant woman was referred for placental mesenchymal dysplasia and fetal omphalocele. Karyotype, array‐CGH and Beckwith‐Wiedemann Syndrome (BWS) testing (methylation‐specific multiplex ligation‐dependent probe amplification (MS‐MLPA) of 11p15) performed on amniocytes were negative. After intrauterine fetal demise, the clinical suspicion persisted and BWS MS‐MLPA was repeated on cultured cells from umbilical cord and amniotic fluid, revealing a mosaicism for KvH19 hypermethylation/KCNQ1OT1:TSS:DMR hypomethylation. These results, along with microsatellite analysis of the BWS region, were consistent with mosaic paternal 11p15 isodisomy. A concurrent maternal contamination exclusion test, analyzing polymorphic microsatellite markers on multiple chromosomes, showed an imbalance in favor of paternal alleles at all examined loci on cultured amniocytes and umbilical cord samples. This led to suspicion of mosaic GWpUPD, later confirmed by SNP‐array, identifying a mosaic genome‐wide paternal isodisomy affecting 60% of fetal cells. The assessment of mosaic GWpUPD requires multiple approaches beyond the current established diagnostic processes, also entertaining possible low‐rate mosaicism. Clinical acumen and an integrated testing approach are the key to a successful diagnosis.